Transcriptomics and microbiome insights reveal the protective mechanism of mulberry-derived postbiotics against inflammation in LPS-induced mice - Abbas, Zaheer; Tong, Yucui; Zhang, Jing; Sammad, Abdul; Wang, Junyong; Ahmad, Baseer; Wei, Xubiao; Si, Dayong; Zhang, Rijun (Frontiers in Immunology, 2025)
BackgroundNatural food-derived bioactive compounds have garnered increasing attention for their potential to modulate immune responses and promote gut health. In particular, compounds like mulberry-derived postbiotics (MDP) may offer novel therapeutic strategies to address inflammation, a key driver of many metabolic disorders.MethodologyThis study examines the protective effects of MDP against inflammation in LPS-induced mice, using transcriptomic and microbiome analyses to explore underlying mechanisms.ResultsMDP pretreatment alleviates LPSinduced villous atrophy and intestinal barrier damage, promoting recovery of intestinal morphology. Transcriptomic profiling revealed significant changes in gene expression, with 983 upregulated and 1220 downregulated genes in the NC vs LPS comparison, and 380 upregulated and 204 downregulated genes in the LPS vs LPS+MDP comparison. Enrichment analysis using GO and KEGG pathways revealed significant associations with transcriptional regulatory activity, and the NOD-like receptor signaling pathway among the differentially expressed genes. Protein-protein interaction analysis identified key genes involved in inflammation and immune regulation, with hub genes like IL6, CXCL10, and MYD88 in the LPS group and CD74, CIITA, and H2-AB1 in the MDP-treated group.ConclusionMicrobiome analysis suggested MDP may also influence gut microbiota composition, supporting systemic immune regulation. These findings highlight MDP’s potential as a food additive for immune modulation and gut health.